2018
DOI: 10.1111/pbr.12635
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of number of pod ‐ and seed ‐ related traits QTLs in soybean

Abstract: Traits related to the number of pods and seeds are important yield factors on soybean. The relationships between phenotype and quantitative trait loci (QTLs) of these traits may reveal the mechanisms underlying productivity. Our study objectives were to analyse phenotypic correlations, detect stable QTLs and identify candidate genes useful for marker‐assisted selection. Phenotypic analyses revealed that NThSP (number of three‐seeded pods) was positively correlated with NPPP (number of pods per plant) and SNPP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 44 publications
3
6
0
Order By: Relevance
“…Either way, for these QTL the alleles that favour pod number originated from the parent 'Sigalia' (Figure d and e). Their position is physically close to a QTL reported by Li et al () for pod number obtained from on‐field experiments (33.43–39.41 Mb). They postulated the gene Glyma.13G223300 (WM82.a2.v1) as a candidate underlying the QTL, which is located less than 600 kb downstream of our pod number QTL.…”
Section: Discussionsupporting
confidence: 88%
“…Either way, for these QTL the alleles that favour pod number originated from the parent 'Sigalia' (Figure d and e). Their position is physically close to a QTL reported by Li et al () for pod number obtained from on‐field experiments (33.43–39.41 Mb). They postulated the gene Glyma.13G223300 (WM82.a2.v1) as a candidate underlying the QTL, which is located less than 600 kb downstream of our pod number QTL.…”
Section: Discussionsupporting
confidence: 88%
“…In PP, most of the genes detected by SVR-mediated GWAS are associated with auxin influx carrier or auxin response factors (ARFs), gibberellin synthesis, and response to brassinosteroid (Lin et al , 2020; Yin et al , 2018). Song et al (2020) and Li et al (2018a) also reported that some genes related to PP were associated with embryo development, stamen development, ovule development, cytokinin biosynthesis, and response gibberellin that we also identified in our study. Soybean seed yield significantly depends on seed number and seed size (Liu et al , 2010; Rotundo et al , 2009).…”
Section: Discussionsupporting
confidence: 80%
“…Soybeans are an important food crop all around the world, and are also a major source of oil and protein ( Singh et al, 2010 ). In recent years, many scholars have worked on yield components, such as the number of grains and pods per plant in order to improve soybean yield ( Li et al, 2018 , 2019 ; Du et al, 2019 ; Song et al, 2020 ). However, the attempts made so far have not fundamentally improved yields ( Zhang et al, 2012 ), so it is essential to find the main factors affecting soybean yields in order to increase them.…”
Section: Introductionmentioning
confidence: 99%